Lead, hemoglobin, zinc protoporphyrin and ferritin concentrations in children - Patrícia H C Rondó; Maria de Fátima H Carvalho; Miriam C Souza; Flávio Moraes (Revista de Saúde Pública)
OBJECTIVE: To assess the relationship of blood lead and hemoglobin, zinc protoporphyrin, and ferritin concentrations in children. METHODS: A cross-sectional study was carried out in 136 anemic and non-anemic children from two rural villages near a lead smelter in Adrianópolis, Southern Brazil, from July to September 2001. Hemoglobin electrophoresis was performed to exclude children with hemoglobin variants and thalassemia syndromes associated with anemia. Lead was determined by atomic absorption spectrophotometry; hemoglobin by automated cell counting; zinc protoporphyrin by hematofluorometry; ferritin by chemiluminescence. Student's t-test, Mann-Whitney test, and the c² test were used to assess the significance of the differences between the variables investigated in anemic and non-anemic children. Stepwise multivariate linear regression analysis was performed using two models for anemic and non-anemic children respectively. RESULTS: Lead was negatively associated to hemoglobin (p<0.017) in the first model, and in the second model lead was positively associated to zinc protoporphyrin (p<0.004) after controlling for ferritin, age, sex, and per capita income. There was an inverse association between hemoglobin and blood lead in anemic children. It was not possible to confirm if anemic children had iron deficiency anemia or subclinical infection, considering that the majority (90.4%) had normal ferritin. CONCLUSIONS: The study detected a relationship between anemia and elevated blood lead concentrations. Further epidemiological studies are necessary to investigate the impact of iron nutritional interventions as an attempt to decrease blood lead in children.